2019
DOI: 10.21276/ijcmr.2019.6.7.30
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cervical Pap Smear with Histopathological Diagnosis in Cervical Lesions: A 2 Years Retrospective Study

Abstract: Introduction: Cervical cancer is one of the most common forms of cancer worldwide. In developing countries, cancer of uterine cervix is ranked second with a relative frequency of 15% of all cancers in women. Screening women with regular Pap smears allows diagnosis of treatable pre-invasive lesions. The objective of the study was to correlate the Pap smear diagnosis with histopathology and to know the accuracy of Pap smears, so as to assess the efficacy of Pap smears in diagnosing cervical lesions. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
1
3
Order By: Relevance
“…8 The present study included 154 pap smear cases who also undergone biopsy or hysterectomy with most patients (35%) in the age group of 41-50 yrs and belong to para 2 (42%) followed by para 3 (25.6%). It has accordance with Sachan et al, 8 and Parija et al 9 The maximum number of patients presented with complaints of whitish discharge per vaginum (42%) and pain lower abdomen (35%) correlates with the study conducted by Bamanikar et al, 10 Atla et al, 11 and Bindroo et al 12 In our study out of 116 cases of NILM, 99% of cases correlated on histopathology which corroborated with the studies done by Atla et al, 11 and Bindroo et al 12 The incidence of Epithelial cell abnormality (ECA) was seen in 18.1% which correlated with Patil et al 13 But this incidence was higher than the study conducted by Malpani et al, 14 this may be because we had small sample size.…”
Section: Discussionsupporting
confidence: 85%
“…8 The present study included 154 pap smear cases who also undergone biopsy or hysterectomy with most patients (35%) in the age group of 41-50 yrs and belong to para 2 (42%) followed by para 3 (25.6%). It has accordance with Sachan et al, 8 and Parija et al 9 The maximum number of patients presented with complaints of whitish discharge per vaginum (42%) and pain lower abdomen (35%) correlates with the study conducted by Bamanikar et al, 10 Atla et al, 11 and Bindroo et al 12 In our study out of 116 cases of NILM, 99% of cases correlated on histopathology which corroborated with the studies done by Atla et al, 11 and Bindroo et al 12 The incidence of Epithelial cell abnormality (ECA) was seen in 18.1% which correlated with Patil et al 13 But this incidence was higher than the study conducted by Malpani et al, 14 this may be because we had small sample size.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we also found ASC-UC in most of the cases, accounting for7.1%. In addition, we found a cytohistological correlation in 56% of cases, with chronic cervicitis and squamous cell metaplasia in most of the patients (64.3%), but lower than the 93% and 91% reported in other studies [9,13]. The LSIL, HSIL and SCC were fully correlated with histopathology in the present study in available data which was comparable to another study [14].…”
Section: Discussionsupporting
confidence: 81%
“…The sensitivity, specificity, PPV, NPV and accuracy of the present study compared with other studies are shown in Table 5. The sensitivity of cervical smears reported in the present study (83.3%) was higher than that reported in other studies [8,10,13,[15][16][17]. The specificity reported in the present study (94.73%) was much higher than that reported by Patil et al, Bamanikar et [8,14,16,17].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Thus, this cancer is preventable and is amenable to detection by screening methods during early preinvasive stage. [6] Timing of diagnosis and extent of disease at the time of diagnosis determine the prognosis in cases of cervical cancer. Early diagnosis and management are associated with less intensive treatment, good outcome and reduced morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%